Analysis of base sector, coefficient of localization and specialization to detect the superiorcommodity of livestock in Regency of South Bolaang Mongondow Provinceof North Sulawesi, Indonesia - Wantasen, Erwin; Umboh, Sintya; Endoh, Eusebius (Faculty of Animal Science, Universitas Brawijaya, 2020)
This study aimed to know the type of the superior commodity of livestock and the structure of livestock growth in Regency of South Bolaang Mongondow, Province of North Sulawesi. This research was performed in three districts, such as District of Bolang Uki, District of Posigadan, and District of Pinolosian, possessing the largest ruminant and non-ruminant livestock population. Nineteen respondents of breeders were randomly selected, consisting of cattle, goat, native chicken, broiler, egg-layer, and duck breeder, respectively 15 respondents. Data collected was then analyzed using analysis of location quotient (LQ), coefficient of localization and specialization. According to the result of location quotient (LQ) analysis, cattle, goat, native chicken, and the duck was the superior commodity, becoming a base sector in Regency of South Bolaang Mongondow obtaining value of LQ >1. From four of the superior commodities, nonetheless, only did cattle have more than one coefficient value of localization (1.020), depicting that cattle had been localized in the study area to sustain the local economy. The analysis of specialization showed that Regency of South Bolaang Mongondow had not self-specialized for certain types of livestock to develop regional economy, presented by the coefficient value of specialization which was still lower than one.